The history of ICSID - Parra, Antonio R. (Oxford : Oxford University Press, 2012)
This title details the history of the International Centre for Settlement of Investment Disputes (ICSID) and its convention covering the years from 1955 to 2010. It includes accounts of the formulation of the convention, the development of ICSID's regulations and rules and analysis of the cases submitted to it over this time.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: International Centre for Settlement of Investment Disputes -- History; Convention on the Settlement of Investment Disputes between States and Nationals of Other States, -- (1965); International commercial arbitration; Investments, Foreign (International law)